Assessing Emergency Preparedness and Response Capacity Using Community Assessment for Public Health Emergency Response Methodology: Portsmouth, Virginia, 2013. (22nd January 2016) - Kurkjian, Katie M.; Winz, Michelle; Yang, Jun; Corvese, Kate; Colón, Ana; Levine, Seth J.; Mullen, Jessica; Ruth, Donna; Anson-Dwamena, Rexford; Bayleyegn, Tesfaye; Chang, David S.
Abstract: Objective: For the past decade, emergency preparedness campaigns have encouraged households to meet preparedness metrics, such as having a household evacuation plan and emergency supplies of food, water, and medication. To estimate current household preparedness levels and to enhance disaster response planning, the Virginia Department of Health with remote technical assistance from the Centers for Disease Control and Prevention conducted a community health assessment in 2013 in Portsmouth, Virginia. Methods: Using the Community Assessment for Public Health Emergency Response (CASPER) methodology with 2-stage cluster sampling, we randomly selected 210 households for in-person interviews. Households were questioned about emergency planning and supplies, information sources during emergencies, and chronic health conditions. Results: Interview teams completed 180 interviews (86%). Interviews revealed that 70% of households had an emergency evacuation plan, 67% had a 3-day supply of water for each member, and 77% had a first aid kit. Most households (65%) reported that the television was the primary source of information during an emergency. Heart disease (54%) and obesity (40%) were the most frequently reported chronic conditions. Conclusions: The Virginia Department of Health identified important gaps in local household preparedness. Data from the assessment have been used to inform community health partners, enhance disaster response planning, set community health priorities, and influence Portsmouth's Community Health Improvement Plan. ( Disaster Med Public Health Preparedness . 2016;10:193–198)